A comparative study on the legal framework of EIA in housing development projects between Malaysia, India, Japan & Hong Kong / Alia Ilani Nasution Abdul Hamid...[et al.] - Abdul Hamid, Alia Ilani Nasution; Jamaludin, Muhammad Haziq; Lazan, Muhammad Raihan; Mokhtar, Nadiah (Faculty of Law, 2014)
This study is done to analyse the legal framework of EIA in housing development projects between Malaysia and Asian countries. This study is also looking to examine Schedule 7 of EIA Order 1987 pertaining to the implementation of EIA on housing development project under Section 34A of the EQA 1974 and to highlight similar laws governing EIA in housing development project in other Asian countries. Qualitative research method was adopted. Documents and online literatures are the sources used to analyse the inadequacy of the laws governing EIA and the primary sources for legal analysis of this research are the statutes, namely; the EQA 1974 and international statutes from other jurisdictions, which are also used for comparative studies between countries. Secondary sources such as online databases in search of literatures for the research are also used. This study is to provide recommendations that may improve the legislative framework for EIA in Malaysia and highlights different jurisdictions of other countries that have different regulations, implementations and penalties in governing EIA. The main focus of this study is to analyse on the relation between the laws governing the EIA under the environmental law in Malaysia and Asian countries, and the legal problem rises pertaining the implementation of EIA in housing development project. It is observed that the Act is not adequate to govern the issues surrounding the legal problem and several recommendations are provided at the end of this study in order to improve the current laws on this matter.